Evaluation of Metabolizable Energy and Crude Protein Balance on Productivity and Income on Male Kamang Ducks - Triani, Hera Dwi; Yuniza, A.; Marlida, Y.; Husmaini, Husmaini; Astuti, W. D. (Jurnal Sain Peternakan Indonesia, 2024)
Male Kamang ducks are one of the local ducks in West Sumatran germplasm originating from Tilatang Kamang and Kamang Magek Districts, Agam Regency, West Sumatera. The balance of metabolizable energy and crude protein (EM/P) in preparing the ration for Kamang ducks must be considered because it is closely related to the efficiency and growth of the ducks. Preparing the feed formulation for Kamang ducks with the right energy and protein balance will support their productivity. The research used male Kamang ducks in the grower phase, which is 3 to 7 weeks of age. Feed Treatment was metabolizable energy of 2800 kcal/kg with 17%, 18%, and 19% crude protein levels. The design used was completely randomized, with 3 treatments and 6 replications. The research showed no significant effect of treatments on feed consumption, body weight gain, or conversion ratio of male Kamang ducks in the grower phase; however, from the treatments, the highest income based on the IOFC value was ration B. In male Kamang ducks, good performance in balance of ME/P are 147.37 to 164.71 with the highest Income Over Feed and Cost (IOFC) value and lower fat abdominal at ME/P 155.55.